Evaluation of the Use of Leaderboards in a Gamified Application for Academic Learning - Dias Macena, Josinaldo; Alves de Araújo, Aislânia; Soares dos Santos, Jucelio (RENOTE, 2021)
In this paper, we analyze the interference of the leaderboards in the number of correct answers in the problem-solving activities present in a gamified application. Also, we checked the usability level of the application with/without leaderboards. In order to achieve these objectives, we applied a study in a test scenario and verified the effect of the leaderboards on the number of correct answers. Then, we applied a survey with the participants to analyze the usability level of the application. As a result, although the level of satisfaction of the participants who used the application with the leaderboards was higher, this difference was not significant. Also, the leaderboards did not influence the number of correct answers to problem-solving.